Risk factors for bloodstream infection in COVID-19 patients in intensive care units: a systematic review and meta-analysis - Jun Wang; Ting Jiang (BMC Infectious Diseases)
Abstract Background Risk factors for bloodstream infection in patients with COVID-19 in the intensive care unit (ICU) remain unclear. The purpose of this systematic review was to study the risk factors for BSI in patients admitted to ICUs for COVID-19. Methods A systematic search was performed on PubMed, EMBASE, Cochrane Library, and Web of Science up to July 2024. Data were reported as combined odds ratio (OR) for categorical variables and weighted mean difference (WMD) for continuous variables. Results 6914 studies were retrieved, of which 55 were included in the meta-analysis. Men (OR = 1.28, 95% CI: 1.10–1.50, P = 0.006), high SAPS II score (WMD = 6.43, 95% CI: 0.23–12.63, P = 0.042), diabetes (OR = 1.34, 95% CI: 1.04–1.73, P = 0.022), tracheal intubation (OR = 8.68, 95% CI: 4.68–16.08, P < 0.001), mechanical ventilation (OR = 22.00, 95% CI: 3.77-128.328, P < 0.001), ECMO (OR = 2.70, 95% CI: 1.17–6.26, P = 0.020), central venous cannulation (OR = 9.33, 95% CI: 3.06–28.43, P < 0.001), prolonged ICU stay (WMD = 10.37, 95% CI: 9.29–11.44, P < 0.001), methylprednisolone use (OR = 2.24, 95% CI: 1.24–4.04, P = 0.008), and the combination of methylprednisolone and Tocilizumab (OR = 4.54, 95% CI: 1.09–18.88, P = 0.037) were risk factors for ICU-BSI in COVID-19 patients. Conclusion We identified 10 risk factors for ICU-BSI in COVID-19 patients. In future studies, these factors can be combined to establish a more comprehensive and accurate prediction model for ICU-BSI in COVID-19 patients. Targeted measures can be taken earlier to control BSI.